An extension of the theory of planned behaviour in predicting intention to reduce plastic use in the Philippines: Cross‐sectional and experimental evidence - Aruta, John Jamir Benzon R. (Asian journal of social psychology, 2022)
The Philippines is the third‐largest contributor to plastic waste, which is an urgent global problem that cannot be addressed without individual and collective behaviour changes. In two studies, the present research examined the antecedents of intention to reduce plastic use in the Philippines. Using a cross‐sectional online survey, Study 1 (N = 245) investigated the influence of attitudes, perceived behavioural control, two types of norms (descriptive and prescriptive norms), gender, and the interaction effect between descriptive norms and gender on Filipinos’ intention to reduce plastic use. Latent variable path analysis revealed that attitudes, perceived behavioural control, prescriptive norms, but not descriptive norms, and gender (and their interaction), significantly predicted plastic reduction intention. Explicating the non‐significant prediction of descriptive norms and gender in Study 1, a 2 (low descriptive versus high descriptive norms) × 2 (males versus females) between‐subjects experiment was conducted in Study 2 (N = 280) to investigate the interaction between descriptive norms and gender on intention to reduce plastic use. Results revealed a significant interaction effect, with descriptive norms fostering intention to reduce plastic use among males, but not among females. Implications for policies towards environmental sustainability in non‐Western countries are discussed.